A corrosion-resistant treatment process for the surface of a remote plasma source cavity

Through the combination of microarc oxidation technology and nano cerium oxide and quaternized amino acid-derived corrosion inhibitors, a high corrosion-resistant oxide film layer is formed, which solves the problem of insufficient corrosion resistance on the surface of the remote plasma source cavity and improves the service life and antibacterial performance of the equipment.

CN118497852BActive Publication Date: 2025-03-18DONGGUAN SHENGDING PRECISION INSTR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410565512.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-03-18
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

The corrosion resistance of the existing remote plasma source cavity surface is insufficient. Traditional anodizing treatment leads to insufficient thickness of the oxide film and is prone to corrosion, affecting the stability of the plasma source and subsequent etching process.

Method used

Microarc oxidation technology is used to replace the traditional anodizing process, and a dense, antibacterial and corrosion-resistant oxide film layer is formed through polishing, de-oiling and microarc oxidation treatment, and nano cerium oxide and quaternized amino acid-derived corrosion inhibitor are introduced to enhance the corrosion resistance of the film layer.

Benefits of technology

Improves corrosion resistance on the surface of the remote plasma source cavity, extends service life, reduces maintenance costs, and exhibits high corrosion resistance and antibacterial properties in acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004829129160000101
    Figure BDA0004829129160000101
Patent Text Reader

Abstract

The invention relates to the technical field of remote plasma source cavities, and in particular to a corrosion-resistant treatment process for the surface of a remote plasma source cavity. A micro-arc oxidation technology is used to replace a traditional anodic oxidation process, and an oxide film layer with a compact structure, antibacterial properties, corrosion resistance and strong bonding with a substrate is prepared on the surface of the remote plasma source cavity. A thermal decomposition stripping method is used, and cobalt salt is used as a dopant to strip stacked CeCO3OH materials into two-dimensional cobalt-doped cerium dioxide nanosheets. Then, the two-dimensional cobalt-doped cerium dioxide nanosheets are used as carriers to in-situ grow a cerium-cobalt bimetallic organic framework with trimesic acid as an organic ligand as a nano container for introducing a corrosion inhibitor. 3,5-dihydroxybenzyl alcohol is used as a raw material to synthesize an alkynyl-terminated quaternary ammonium copolymer, and then the alkynyl-terminated quaternary ammonium copolymer is grafted with L-cysteine ​​through a click reaction to obtain a quaternary amino acid-derived corrosion inhibitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of remote plasma source cavities, in particular to a corrosion-resistant treatment process for the surface of a remote plasma source cavity. Background Art

[0002] In the microelectronics industry, nitrogen trifluoride is a plasma etching gas that will split into active fluorine ions during ion etching, selectively etches silicon and tungsten, and leaves no residue on the surface after etching. Compared with traditional fluorocarbon etching processes, it has the advantages of faster cleaning time, reduced greenhouse gas emissions, and effectively avoiding damage to the equipment chamber. It is increasingly used in etching processes, such as for cleaning chemical vapor deposition chambers in semiconductor manufacturing.

[0003] In the prior art, the equipment used to separate nitrogen trifluoride and generate fluorine atoms in plasma state is a remote plasma source cavity. In order to make the remote plasma source cavity have functions such as gas conduction, power supply, and cooling, it is often prepared with aluminum alloy as raw material. Since the wear and corrosion resistance of the aluminum alloy material itself cannot meet the use environment of nitrogen trifluoride, it is of practical significance to perform surface treatment on the inner cavity components.

[0004] Traditionally, the surface of the cavity is mostly treated by anodizing. Generally, in order to improve the corrosion resistance and voltage breakdown resistance of the oxide film, the thickness of the anodized film needs to reach more than 50μm, which is prone to microcracks, thereby accelerating the corrosion of the cavity surface, destroying the stable output of the plasma source, and being unfavorable for subsequent etching processes. Summary of the invention

[0005] The purpose of the present invention is to provide a remote plasma source cavity surface corrosion resistance treatment process to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A remote plasma source cavity surface corrosion resistance treatment process, comprising the following steps:

[0008] S1: Grind and polish the cavity to make the surface roughness of the cavity 0.2-0.8μm;

[0009] S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity;

[0010] S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product.

[0011] Furthermore, the working conditions of degreasing cleaning are: the cleaning liquid is one of acetone or ethanol, the cleaning temperature is 25-40° C., and the cleaning time is 10-20 minutes.

[0012] Furthermore, the composition of the treatment liquid is: deionized water as solvent, wherein sodium silicate 10-40 g / L, sodium citrate 30-50 g / L, sodium borate 10-15 g / L, sodium hydroxide 5-10 g / L, and the temperature is 25-60°C.

[0013] Furthermore, the working conditions of micro-arc oxidation are: forward current density 2-5A / dm 2 , duty cycle 20-40%; reverse current density 1-3A / dm 2 , duty cycle 30-50%, power pulse frequency 100-300Hz, working time 60-90min.

[0014] Furthermore, the treatment liquid comprises: deionized water as solvent, 10-40 g / L sodium silicate, 1-1.5 g / L composite nano cerium oxide, 30-50 g / L sodium citrate, 10-15 g / L sodium borate, 5-10 g / L sodium hydroxide, and the temperature is 25-60°C.

[0015] Furthermore, the preparation of composite nano-cerium oxide includes the following steps:

[0016] (1) Using copper foam as a substrate, ultrasonically cleaning with acetone, deionized water, and ethanol for 10-15 minutes in sequence; mixing cobalt acetate tetrahydrate, cerium nitrate hexahydrate, hexamethylenetetramine, ethanol, and ethylene glycol, stirring for 20-30 minutes to obtain a precursor solution, transferring it to a reaction kettle, keeping it at 168-172° C. for 6-8 hours, and cooling it to 18-25° C.; ultrasonically rinsing the copper foam and the reaction kettle with ethanol, centrifuging the rinse liquid for 3-5 times, drying it, calcining it at 395-405° C. in an air atmosphere for 4 hours, and cooling it to obtain cobalt-doped cerium oxide nanosheets;

[0017] (2) mixing cobalt-doped cerium oxide nanosheets, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, N,N-dimethylformamide, anhydrous ethanol, and deionized water, adding trimesic acid and polyvinyl pyrrolidone, stirring for 20-30 minutes, transferring to a microwave reactor, keeping the temperature at 150° C. for 25-30 minutes, cooling, centrifuging, washing, and drying to obtain modified nano-cerium oxide;

[0018] (3) The modified nano-cerium oxide, the quaternized amino acid-derived corrosion inhibitor and acetone are mixed, ultrasonically treated for 10-20 minutes, transferred to a vacuum environment and placed for 15-20 minutes, the air pressure is reduced to 0.05-0.08 MPa, and kept at 30-40° C. for 1-2 hours to obtain composite nano-cerium oxide.

[0019] Furthermore, the mass volume ratio of the modified nano-cerium oxide, the quaternized amino acid-derived corrosion inhibitor and acetone is 4 g:17 g:250 mL.

[0020] Further, the preparation of the quaternized amino acid derived corrosion inhibitor comprises the following steps:

[0021] 1) Under a nitrogen atmosphere, acetone, 3,5-dihydroxybenzyl alcohol and potassium carbonate are mixed, refluxed for 20-30 minutes, cooled to 18-25° C., 3-(dimethylamino) chloropropane hydrochloride and 18-crown ether-6 are added, refluxed for 70-72 hours, cooled, filtered, deionized water is added, the aqueous phase is extracted with dichloromethane, rotary evaporated, dichloromethane is added, washed, dried, filtered, rotary evaporated, and separated by silica gel column chromatography using methanol and dichloromethane in a volume ratio of 1:1 to obtain 3-[3-(dimethylamino) propoxy] benzyl alcohol;

[0022] 2) Sodium hydride and tetrahydrofuran are mixed, cooled to 0°C, a mixed solution of 3-[3-(dimethylamino)propoxy]benzyl alcohol and N,N-dimethylformamide is added, stirred for 1-2 hours, heated to 18-25°C and stirred for 1-2 hours, a mixed solution of 3-bromopropyne and tetrahydrofuran is added, heated to 28-32°C and kept warm for 14-16 hours, transferred to an ice bath, saturated ammonium chloride solution is added until no bubbles are generated, the organic phase is separated, the aqueous phase is extracted with dichloromethane, rotary evaporated, dichloromethane is added, washed with water, dried, gradient column chromatography is performed using dichloromethane, methanol, and triethylamine in a volume ratio of 20:1:1, rotary evaporated, and dried to obtain an intermediate preparation;

[0023] 3) Mix the intermediate preparation, methanol and methyl iodide, reflux for 70-72 hours, cool to 18-25° C., add ethyl acetate, add anhydrous methanol, add ethyl acetate, wash and dry to obtain an alkynyl-terminated quaternary ammonium copolymer;

[0024] 4) Under argon protection, the quaternary ammonium copolymer terminated with alkynyl, 2-hydroxy-2-methyl-1-phenyl-1-propanone, N-methylpyrrolidone and tetrahydrofuran are mixed, a mixed solution of L-cysteine ​​and deionized water is added, ultraviolet light is applied, vacuum distillation is performed, washing is performed, and drying is performed to obtain a quaternary amino acid derivative corrosion inhibitor.

[0025] Furthermore, the working conditions of ultraviolet irradiation are: irradiation under 365nm ultraviolet lamp for 15-20min.

[0026] Furthermore, the mass ratio of the quaternary ammonium copolymer terminated with alkynyl groups to L-cysteine ​​is 4:2.1.

[0027] Beneficial effects of the present invention:

[0028] The present invention provides a corrosion-resistant treatment process for the surface of a remote plasma source cavity, which replaces the traditional anodizing process with a micro-arc oxidation technology, and prepares an oxide film layer with a dense structure, antibacterial and corrosion-resistant structure, and strong bonding with a substrate on the surface of the remote plasma source cavity, thereby increasing the service life of the remote plasma source cavity and reducing maintenance costs.

[0029] By controlling the process parameters of micro-arc oxidation, a uniform oxide layer is formed on the surface of the aluminum alloy. In order to further improve the hardness and corrosion resistance of the oxide layer, nano-cerium oxide is introduced to seal the micro-nano pores on the surface of the oxide layer, so that the surface of the oxide film becomes smoother, the porosity of the oxide film is reduced, and the corrosion resistance of the film is enhanced. In order to increase the mobility of nano-cerium oxide in the micro-arc oxidation treatment solution, the present invention uses a thermal decomposition stripping method and uses cobalt salt as a dopant to seal the stacked CeCO 3 The OH material is stripped into two-dimensional cobalt-doped cerium dioxide nanosheets, and then the two-dimensional cobalt-doped cerium dioxide nanosheets are used as carriers to in situ grow a cerium-cobalt bimetallic organic framework with trimesic acid as an organic ligand. Its unique configuration not only improves the corrosion resistance of the oxide film layer, but also serves as a nanocontainer for introducing corrosion inhibitors.

[0030] In order to further improve the corrosion resistance of the cavity in an acidic environment, the present invention uses natural amino acids as raw materials to construct a highly corrosion-resistant and antibacterial green corrosion inhibitor, and uses 3,5-dihydroxybenzyl alcohol as a raw material to synthesize an alkynyl-terminated quaternary ammonium copolymer containing two cationic functional groups, and then the alkynyl-terminated quaternary ammonium copolymer is grafted with L-cysteine ​​through a click reaction to obtain a quaternary amino acid-derived corrosion inhibitor, which is added into an oxide film layer as an intercalant or functional component to construct a highly corrosion-resistant and antibacterial oxide film layer, which can not only achieve efficient protection of the cavity, but also meet the needs of sustainable social development. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0034] Embodiment 1: A process for treating the surface of a remote plasma source cavity for corrosion resistance, comprising the following steps:

[0035] S1: Grind and polish the cavity to make the surface roughness of the cavity 0.6μm;

[0036] S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity;

[0037] S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product;

[0038] The working conditions for degreasing cleaning are: cleaning liquid is acetone, cleaning temperature is 40°C, and cleaning time is 10 min;

[0039] The composition of the treatment solution is: deionized water as solvent, including 40g / L sodium silicate, 50g / L sodium citrate, 15g / L sodium borate, 10g / L sodium hydroxide, and the temperature is 60°C;

[0040] The working conditions of micro-arc oxidation are: forward current density 5A / dm 2 , duty cycle 40%; reverse current density 3A / dm 2 , duty cycle 50%, power pulse frequency 300Hz, working time is 60min.

[0041] Embodiment 2: A process for treating the surface of a remote plasma source cavity for corrosion resistance, comprising the following steps:

[0042] S1: Grind and polish the cavity to make the surface roughness of the cavity 0.6μm;

[0043] S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity;

[0044] S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product;

[0045] The working conditions for degreasing cleaning are: cleaning liquid is acetone, cleaning temperature is 25°C, and cleaning time is 20min;

[0046] The working conditions of micro-arc oxidation are: forward current density 2A / dm 2 , duty cycle 20%; reverse current density 1A / dm 2 , duty cycle 30%, power pulse frequency 100Hz, working time 90min;

[0047] The composition of the treatment liquid is: deionized water as solvent, including 10g / L sodium silicate, 1g / L composite nano cerium oxide, 30g / L sodium citrate, 10g / L sodium borate, 5g / L sodium hydroxide, and the temperature is 25°C;

[0048] The preparation of composite nano cerium oxide includes the following steps:

[0049] (1) Using copper foam as a substrate, ultrasonically cleaning with acetone, deionized water, and ethanol for 10 minutes in sequence; mixing 0.5 mmol of cobalt acetate tetrahydrate, 1.5 mmol of cerium nitrate hexahydrate, 125 mg of hexamethylenetetramine, 7 mL of ethanol, and 6.5 mL of ethylene glycol, stirring for 20 minutes to obtain a precursor solution, transferring it to a reactor, keeping it at 168°C for 8 hours, and cooling it to 18°C; ultrasonically washing the copper foam and the reactor with ethanol, centrifuging the washing liquid 3 times, drying it, calcining it at 395°C in an air atmosphere for 4 hours, and cooling it to obtain cobalt-doped cerium oxide nanosheets;

[0050] (2) 0.5 g of cobalt-doped cerium oxide nanosheets, 1 g of cobalt nitrate hexahydrate, 1.6 g of cerium nitrate, 20 mL of N,N-dimethylformamide, 20 mL of anhydrous ethanol, and 20 mL of deionized water were mixed, 0.3 g of trimesic acid and 1 g of polyvinyl pyrrolidone were added, and the mixture was stirred for 20 min, and then transferred to a microwave reactor, kept at 150° C. for 25 min, cooled, centrifuged, washed, and dried to obtain modified nano-cerium oxide;

[0051] (3) 4 g of modified nano-cerium oxide, 17 g of quaternized amino acid-derived corrosion inhibitor and 250 mL of acetone were mixed, ultrasonically treated for 10 min, transferred to a vacuum environment and placed for 15 min, the gas pressure was reduced to 0.05 MPa, and kept at 30 ° C for 2 h to obtain composite nano-cerium oxide;

[0052] The preparation of the quaternized amino acid derived corrosion inhibitor comprises the following steps:

[0053] 1) Under a nitrogen atmosphere, 40 mL of acetone, 1 g of 3,5-dihydroxybenzyl alcohol, and 1.8 g of potassium carbonate were mixed, refluxed for 20 min, cooled to 18°C, 0.95 g of 3-(dimethylamino)chloropropane hydrochloride and 0.17 g of 18-crown ether-6 were added, refluxed for 70 h, cooled, filtered, 10 mL of deionized water was added, the aqueous phase was extracted with dichloromethane, rotary evaporated, 15 mL of dichloromethane was added, washed, dried, filtered, rotary evaporated, and separated by silica gel column chromatography using methanol and dichloromethane in a volume ratio of 1:1 to obtain 3-[3-(dimethylamino)propoxy]benzyl alcohol;

[0054] 2) Mix 0.7 g of sodium hydride and 10 mL of tetrahydrofuran, cool to 0°C, add a mixed solution of 2 g of 3-[3-(dimethylamino)propoxy]benzyl alcohol and 2.5 mL of N,N-dimethylformamide, stir for 1 h, heat to 18°C ​​and stir for 2 h, add a mixed solution of 0.5 g of 3-bromopropyne and 1.5 mL of tetrahydrofuran, heat to 28°C and keep warm for 16 h, transfer to an ice bath, add saturated ammonium chloride solution until no bubbles are generated, separate the organic phase, extract the aqueous phase with dichloromethane, rotary evaporate, add 10 mL of dichloromethane, wash with water, dry, perform gradient column chromatography using dichloromethane, methanol, and triethylamine in a volume ratio of 20:1:1, rotary evaporate, and dry to obtain an intermediate preparation;

[0055] 3) 0.51 g of the intermediate preparation, 10 mL of methanol, and 9 g of methyl iodide were mixed, refluxed for 70 h, cooled to 18° C., 200 mL of ethyl acetate was added, 4 mL of anhydrous methanol was added, 100 mL of ethyl acetate was added, washed, and dried to obtain an alkynyl-terminated quaternary ammonium copolymer;

[0056] 4) Under argon protection, 4 g of the alkynyl-terminated quaternary ammonium copolymer, 105 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 100 mL of N-methylpyrrolidone, and 300 mL of tetrahydrofuran were mixed, and a mixture of 2.1 g of L-cysteine ​​and 100 mL of deionized water was added, and the mixture was irradiated with ultraviolet light, distilled under reduced pressure, washed, and dried to obtain a quaternary amino acid derivative corrosion inhibitor; the working conditions of ultraviolet light irradiation were: irradiation under a 365 nm ultraviolet lamp for 15 min.

[0057] Embodiment 3: A process for treating the surface of a remote plasma source cavity for corrosion resistance, comprising the following steps:

[0058] S1: Grind and polish the cavity to make the surface roughness of the cavity 0.6μm;

[0059] S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity;

[0060] S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product;

[0061] The working conditions for degreasing cleaning are: the cleaning liquid is ethanol, the cleaning temperature is 30°C, and the cleaning time is 15 min;

[0062] The working conditions of micro-arc oxidation are: forward current density 3A / dm 2 , duty cycle 30%; reverse current density 2A / dm 2 , duty cycle 40%, power pulse frequency 200Hz, working time 70min;

[0063] The composition of the treatment liquid is: deionized water as solvent, including 20g / L sodium silicate, 1.2g / L composite nano cerium oxide, 40g / L sodium citrate, 12g / L sodium borate, 8g / L sodium hydroxide, and the temperature is 40°C;

[0064] The preparation of composite nano cerium oxide includes the following steps:

[0065] (1) Using copper foam as a substrate, ultrasonically cleaning with acetone, deionized water, and ethanol for 12 minutes in sequence; mixing 0.5 mmol of cobalt acetate tetrahydrate, 1.5 mmol of cerium nitrate hexahydrate, 125 mg of hexamethylenetetramine, 7 mL of ethanol, and 6.5 mL of ethylene glycol, stirring for 25 minutes to obtain a precursor solution, transferring it to a reactor, keeping it at 170°C for 7 hours, and cooling it to 20°C; ultrasonically washing the copper foam and the reactor with ethanol, centrifuging the washing liquid 4 times, drying it, calcining it at 400°C in an air atmosphere for 4 hours, and cooling it to obtain cobalt-doped cerium oxide nanosheets;

[0066] (2) 0.5 g of cobalt-doped cerium oxide nanosheets, 1 g of cobalt nitrate hexahydrate, 1.6 g of cerium nitrate, 20 mL of N,N-dimethylformamide, 20 mL of anhydrous ethanol, and 20 mL of deionized water were mixed, 0.3 g of trimesic acid and 1 g of polyvinyl pyrrolidone were added, and the mixture was stirred for 25 min, and then transferred to a microwave reactor, kept at 150 ° C for 28 min, cooled, centrifuged, washed, and dried to obtain modified nano-cerium oxide;

[0067] (3) 4 g of modified nano-cerium oxide, 17 g of quaternized amino acid-derived corrosion inhibitor and 250 mL of acetone were mixed, ultrasonically treated for 15 min, transferred to a vacuum environment and placed for 18 min, the gas pressure was reduced to 0.06 MPa, and kept at 35 ° C for 1.5 h to obtain composite nano-cerium oxide;

[0068] The preparation of the quaternized amino acid derived corrosion inhibitor comprises the following steps:

[0069] 1) Under nitrogen atmosphere, 40 mL of acetone, 1 g of 3,5-dihydroxybenzyl alcohol, and 1.8 g of potassium carbonate were mixed for 15 min, refluxed for 25 min, cooled to 20°C, 0.95 g of 3-(dimethylamino)chloropropane hydrochloride and 0.17 g of 18-crown ether-6 were added, refluxed for 71 h, cooled, filtered, 10 mL of deionized water was added, the aqueous phase was extracted with dichloromethane, rotary evaporated, 15 mL of dichloromethane was added, washed, dried, filtered, rotary evaporated, and separated by silica gel column chromatography using methanol and dichloromethane in a volume ratio of 1:1 to obtain 3-[3-(dimethylamino)propoxy]benzyl alcohol;

[0070] 2) Mix 0.7 g of sodium hydride and 10 mL of tetrahydrofuran, cool to 0°C, add a mixed solution of 2 g of 3-[3-(dimethylamino)propoxy]benzyl alcohol and 2.5 mL of N,N-dimethylformamide, stir for 1.5 h, heat to 20°C and stir for 1.5 h, add a mixed solution of 0.5 g of 3-bromopropyne and 1.5 mL of tetrahydrofuran, heat to 30°C and keep warm for 15 h, transfer to an ice bath, add saturated ammonium chloride solution until no bubbles are generated, separate the organic phase, extract the aqueous phase with dichloromethane, rotary evaporate, add 10 mL of dichloromethane, wash with water, dry, perform gradient column chromatography using dichloromethane, methanol, and triethylamine in a volume ratio of 20:1:1, rotary evaporate, and dry to obtain an intermediate preparation;

[0071] 3) 0.51 g of the intermediate preparation, 10 mL of methanol and 9 g of methyl iodide were mixed, refluxed for 71 h, cooled to 20° C., 200 mL of ethyl acetate was added, 4 mL of anhydrous methanol was added, 100 mL of ethyl acetate was added, washed and dried to obtain an alkynyl-terminated quaternary ammonium copolymer;

[0072] 4) Under argon protection, 4 g of the alkynyl-terminated quaternary ammonium copolymer, 105 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 100 mL of N-methylpyrrolidone, and 300 mL of tetrahydrofuran were mixed, and a mixture of 2.1 g of L-cysteine ​​and 100 mL of deionized water was added, and the mixture was irradiated with ultraviolet light, distilled under reduced pressure, washed, and dried to obtain a quaternary amino acid derivative corrosion inhibitor; the working conditions of ultraviolet light irradiation were: irradiation under a 365 nm ultraviolet lamp for 18 min.

[0073] Embodiment 4: A process for treating the surface of a remote plasma source cavity for corrosion resistance, comprising the following steps:

[0074] S1: Grind and polish the cavity to make the surface roughness of the cavity 0.6μm;

[0075] S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity;

[0076] S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product;

[0077] The working conditions for degreasing cleaning are: the cleaning liquid is ethanol, the cleaning temperature is 40°C, and the cleaning time is 10 min;

[0078] The working conditions of micro-arc oxidation are: forward current density 5A / dm 2 , duty cycle 40%; reverse current density 3A / dm 2 , duty cycle 50%, power pulse frequency 300Hz, working time 60min;

[0079] The composition of the treatment liquid is: deionized water as solvent, including 40g / L sodium silicate, 1.5g / L composite nano cerium oxide, 50g / L sodium citrate, 15g / L sodium borate, 10g / L sodium hydroxide, and the temperature is 60°C;

[0080] The preparation of composite nano cerium oxide includes the following steps:

[0081] (1) Using copper foam as a substrate, ultrasonically cleaning with acetone, deionized water, and ethanol for 15 minutes in sequence; mixing 0.5 mmol of cobalt acetate tetrahydrate, 1.5 mmol of cerium nitrate hexahydrate, 125 mg of hexamethylenetetramine, 7 mL of ethanol, and 6.5 mL of ethylene glycol, stirring for 30 minutes to obtain a precursor solution, transferring it to a reactor, keeping it at 172°C for 6 hours, and cooling it to 25°C; ultrasonically washing the copper foam and the reactor with ethanol, centrifuging the washing liquid for 5 times, drying it, calcining it at 405°C in an air atmosphere for 4 hours, and cooling it to obtain cobalt-doped cerium oxide nanosheets;

[0082] (2) 0.5 g of cobalt-doped cerium oxide nanosheets, 1 g of cobalt nitrate hexahydrate, 1.6 g of cerium nitrate, 20 mL of N,N-dimethylformamide, 20 mL of anhydrous ethanol, and 20 mL of deionized water were mixed, 0.3 g of trimesic acid and 1 g of polyvinyl pyrrolidone were added, and the mixture was stirred for 30 min, and then transferred to a microwave reactor, kept at 150° C. for 30 min, cooled, centrifuged, washed, and dried to obtain modified nano-cerium oxide;

[0083] (3) 4 g of modified nano-cerium oxide, 17 g of quaternized amino acid-derived corrosion inhibitor and 250 mL of acetone were mixed, ultrasonically treated for 20 min, transferred to a vacuum environment and placed for 20 min, the gas pressure was reduced to 0.08 MPa, and kept at 40 ° C for 1 h to obtain composite nano-cerium oxide;

[0084] The preparation of the quaternized amino acid derived corrosion inhibitor comprises the following steps:

[0085] 1) Under a nitrogen atmosphere, 40 mL of acetone, 1 g of 3,5-dihydroxybenzyl alcohol, and 1.8 g of potassium carbonate were mixed, refluxed for 20 min, cooled to 25° C., 0.95 g of 3-(dimethylamino)chloropropane hydrochloride and 0.17 g of 18-crown ether-6 were added, refluxed for 72 h, cooled, filtered, 10 mL of deionized water was added, the aqueous phase was extracted with dichloromethane, rotary evaporated, 15 mL of dichloromethane was added, washed, dried, filtered, rotary evaporated, and separated by silica gel column chromatography using methanol and dichloromethane in a volume ratio of 1:1 to obtain 3-[3-(dimethylamino)propoxy]benzyl alcohol;

[0086] 2) Mix 0.7 g of sodium hydride and 10 mL of tetrahydrofuran, cool to 0°C, add a mixed solution of 2 g of 3-[3-(dimethylamino)propoxy]benzyl alcohol and 2.5 mL of N,N-dimethylformamide, stir for 2 h, heat to 25°C and stir for 1 h, add a mixed solution of 0.5 g of 3-bromopropyne and 1.5 mL of tetrahydrofuran, heat to 32°C and keep warm for 14 h, transfer to an ice bath, add saturated ammonium chloride solution until no bubbles are generated, separate the organic phase, extract the aqueous phase with dichloromethane, rotary evaporate, add 10 mL of dichloromethane, wash with water, dry, perform gradient column chromatography using dichloromethane, methanol, and triethylamine in a volume ratio of 20:1:1, rotary evaporate, and dry to obtain an intermediate preparation;

[0087] 3) 0.51 g of the intermediate preparation, 10 mL of methanol, and 9 g of methyl iodide were mixed, refluxed for 72 h, cooled to 18° C., 200 mL of ethyl acetate was added, 4 mL of anhydrous methanol was added, and 100 mL of ethyl acetate was added, washed, and dried to obtain an alkynyl-terminated quaternary ammonium copolymer;

[0088] 4) Under argon protection, 4 g of the alkynyl-terminated quaternary ammonium copolymer, 105 mg of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 100 mL of N-methylpyrrolidone, and 300 mL of tetrahydrofuran were mixed, and a mixture of 2.1 g of L-cysteine ​​and 100 mL of deionized water was added, and the mixture was irradiated with ultraviolet light, distilled under reduced pressure, washed, and dried to obtain a quaternary amino acid derivative corrosion inhibitor; the working conditions of ultraviolet light irradiation were: irradiation under a 365 nm ultraviolet lamp for 20 min.

[0089] Comparative Example 1: Taking Example 4 as the control group, the composite nano-cerium oxide was replaced with cobalt-doped cerium oxide nanosheets, and the other processes were normal.

[0090] Comparative Example 2: Using Example 4 as the control group, L-cysteine ​​was used to replace the quaternary ammonium amino acid derived corrosion inhibitor, and the other processes were normal.

[0091] The material of the cavity in the embodiment and the comparative example is aluminum alloy AL6061, and its hardness is 40HRC.

[0092] Sources of raw materials used (for demonstration purposes only):

[0093] Foam copper DPH: Kunshan Daipinghu Electronic Technology Co., Ltd.; sodium silicate S302432, sodium citrate S189183, sodium borate S474515, cobalt acetate tetrahydrate C433113, cerium nitrate hexahydrate C105376, hexamethylenetetramine H330914, ethylene glycol E103319, cobalt nitrate hexahydrate C112729, N,N-dimethylformamide D111999, trimesic acid T109692, polyvinyl pyrrolidone P434440, 3,5-dihydroxybenzyl alcohol D123605, 3-(di (Methylamino) chloropropane hydrochloride D154697, 18-crown ether-6C105797, sodium hydride S110860, tetrahydrofuran T431413, 3-bromopropyne P106961, triethylamine T103285, 2-hydroxy-2-methyl-1-phenyl-1-propanone B105178, N-methylpyrrolidone M100588, L-cysteine ​​C108237: Aladdin reagent; acetone, sodium hydroxide, ethanol, potassium carbonate, dichloromethane, methanol, ammonium chloride, methyl iodide, ethyl acetate, analytical grade: Sinopharm reagent.

[0094] Performance test: Test the finished products in the embodiments and comparative examples:

[0095] Thickness: refer to GB / T4957-2003, and use eddy current thickness gauge for testing; Microhardness: refer to GB / T4340-2012, and use micro Vickers hardness tester for hardness testing; Antibacterial property: refer to GB / T21866-2008 for testing, and use Escherichia coli AS1.90 as the bacterial species. After 24 hours of culture, the number of live bacteria on the surface is tested, and the antibacterial rate is calculated; Salt spray resistance: refer to GB / T10125-2012 for acid salt spray test, the temperature in the salt spray chamber is 25℃, and the collection liquid is prepared with sodium chloride, glacial acetic acid, and deionized water, in which the sodium chloride concentration is 55g / L, and the solution pH is adjusted to 3.1 with glacial acetic acid. If there is no change in the salt spray test for 240h, it is qualified; if there is no change in the salt spray test for 480h, it is excellent; the results are shown in Table 1;

[0096] Table 1

[0097]

[0098] The present invention provides a corrosion-resistant treatment process for the surface of a remote plasma source cavity, in which a micro-arc oxidation technology is used to replace a traditional anodizing process, and an oxide film layer with a dense structure, antibacterial properties, corrosion resistance, and strong bonding with a substrate is prepared on the surface of the remote plasma source cavity, thereby increasing the service life of the remote plasma source cavity and reducing maintenance costs. In Table 1, / indicates that the item has not been tested.

[0099] By comparing Example 4 with Comparative Example 1, it can be seen that a uniform oxide layer is formed on the surface of the aluminum alloy by controlling the process parameters of micro-arc oxidation. In order to further improve the hardness and corrosion resistance of the oxide layer, nano-cerium oxide is introduced to seal the micro-nano pores on the surface of the oxide layer, so that the surface of the oxide film becomes smoother, the porosity of the oxide film is reduced, and the corrosion resistance of the film is enhanced. In order to increase the mobility of nano-cerium oxide in the micro-arc oxidation treatment solution, the present invention uses a thermal decomposition stripping method and uses cobalt salt as a dopant to seal the stacked CeCO 3 The OH material is stripped into two-dimensional cobalt-doped cerium dioxide nanosheets, and then the two-dimensional cobalt-doped cerium dioxide nanosheets are used as carriers to in situ grow a cerium-cobalt bimetallic organic framework with trimesic acid as an organic ligand. Its unique configuration not only improves the corrosion resistance of the oxide film layer, but also serves as a nanocontainer for introducing subsequent corrosion inhibitors.

[0100] By comparing Example 4 with Comparative Example 2, it can be seen that in order to further improve the corrosion resistance of the cavity in an acidic environment, the present invention uses natural amino acids as raw materials to construct a highly corrosion-resistant, antibacterial green and environmentally friendly corrosion inhibitor, and uses 3,5-dihydroxybenzyl alcohol as a raw material to synthesize an alkynyl-terminated quaternary ammonium copolymer containing two cationic functional groups, and then the alkynyl-terminated quaternary ammonium copolymer is grafted with L-cysteine ​​through a click reaction to obtain a quaternary ammonium amino acid derivative corrosion inhibitor, which is added to the oxide film layer as an intercalant or functional component to construct a highly corrosion-resistant and antibacterial oxide film layer, which can not only achieve efficient protection of the cavity, but also meet the needs of social sustainable development.

[0101] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A remote plasma source cavity surface corrosion resistance treatment process, characterized in that: The following steps are involved: S1: Grind and polish the cavity to make the surface roughness of the cavity 0.2-0.8μm; S2: Degreasing and cleaning the polished cavity to obtain a pre-treated cavity; S3: placing the pretreatment chamber into the treatment liquid, performing micro-arc oxidation treatment, cleaning and drying to obtain a finished product; The composition of the treatment liquid is: deionized water as solvent, including 10-40g / L sodium silicate, 1-1.5g / L composite nano cerium oxide, 30-50g / L sodium citrate, 10-15g / L sodium borate, 5-10g / L sodium hydroxide, and the temperature is 25-60°C; The preparation of the composite nano cerium oxide comprises the following steps: (1) Using copper foam as a substrate, ultrasonically cleaning with acetone, deionized water, and ethanol for 10-15 minutes in sequence; mixing cobalt acetate tetrahydrate, cerium nitrate hexahydrate, hexamethylenetetramine, ethanol, and ethylene glycol, stirring for 20-30 minutes to obtain a precursor solution, transferring it to a reactor, keeping it at 168-172°C for 6-8 hours, and cooling it to 18-25°C; ultrasonically rinsing the copper foam and the reactor with ethanol, centrifuging the rinse liquid for 3-5 times, drying it, calcining it at 395-405°C in an air atmosphere for 4 hours, and cooling it to obtain cobalt-doped cerium oxide nanosheets; (2) mixing cobalt-doped cerium oxide nanosheets, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, N,N-dimethylformamide, anhydrous ethanol, and deionized water, adding trimesic acid and polyvinyl pyrrolidone, stirring for 20-30 minutes, transferring to a microwave reactor, keeping the temperature at 150° C. for 25-30 minutes, cooling, centrifuging, washing, and drying to obtain modified nano-cerium oxide; (3) Mixing the modified nano-cerium oxide, the quaternized amino acid-derived corrosion inhibitor and acetone, ultrasonically treating for 10-20 minutes, transferring to a vacuum environment and placing for 15-20 minutes, reducing the gas pressure to 0.05-0.08 MPa, and keeping the mixture at 30-40° C. for 1-2 hours to obtain composite nano-cerium oxide; The preparation of the quaternized amino acid derived corrosion inhibitor comprises the following steps: 1) Under a nitrogen atmosphere, acetone, 3,5-dihydroxybenzyl alcohol and potassium carbonate were mixed, refluxed for 20-30 minutes, cooled to 18-25°C, 3-(dimethylamino) chloropropane hydrochloride and 18-crown ether-6 were added, refluxed for 70-72 hours, cooled, filtered, deionized water was added, the aqueous phase was extracted with dichloromethane, rotary evaporated, dichloromethane was added, washed, dried, filtered, rotary evaporated, and separated by silica gel column chromatography using methanol and dichloromethane in a volume ratio of 1:1 to obtain 3-[3-(dimethylamino) propoxy] benzyl alcohol; 2) Mix sodium hydride and tetrahydrofuran, cool to 0°C, add a mixed solution of 3-[3-(dimethylamino)propoxy]benzyl alcohol and N,N-dimethylformamide, stir for 1-2h, heat to 18-25°C and stir for 1-2h, add a mixed solution of 3-bromopropyne and tetrahydrofuran, heat to 28-32°C and keep warm for 14-16h, transfer to an ice bath, add saturated ammonium chloride solution until no bubbles are generated, separate the organic phase, extract the aqueous phase with dichloromethane, rotary evaporate, add dichloromethane, wash with water, dry, perform gradient column chromatography with dichloromethane, methanol, and triethylamine in a volume ratio of 20:1:1, rotary evaporate, and dry to obtain an intermediate preparation; 3) The intermediate preparation, methanol and methyl iodide are mixed, refluxed for 70-72 hours, cooled to 18-25°C, ethyl acetate, anhydrous methanol and ethyl acetate are added in sequence, washed and dried to obtain an alkynyl-terminated quaternary ammonium copolymer; 4) Under argon protection, the quaternary ammonium copolymer terminated with alkynyl, 2-hydroxy-2-methyl-1-phenyl-1-propanone, N-methylpyrrolidone and tetrahydrofuran are mixed, a mixture of L-cysteine ​​and deionized water is added, ultraviolet light is applied, vacuum distillation is performed, washing is performed, and drying is performed to obtain a quaternary amino acid derivative corrosion inhibitor.

2. A remote plasma source cavity surface corrosion resistance treatment process according to claim 1, characterized in that: The working conditions for degreasing cleaning are: the cleaning liquid is one of acetone or ethanol, the cleaning temperature is 25-40℃, and the cleaning time is 10-20min.

3. The corrosion resistance treatment process for the surface of a remote plasma source cavity according to claim 1, characterized in that: The working conditions of micro-arc oxidation treatment are: forward current density 2-5A / dm 2 , duty cycle 20-40%; reverse current density 1-3A / dm 2 , duty cycle 30-50%, power pulse frequency 100-300Hz, working time 60-90min.

4. The corrosion resistance treatment process for the surface of a remote plasma source cavity according to claim 1, characterized in that: In the preparation of composite nano-cerium oxide, the mass volume ratio of modified nano-cerium oxide, quaternized amino acid-derived corrosion inhibitor and acetone is 4g:17g:250mL.

5. The corrosion resistance treatment process for the surface of a remote plasma source chamber according to claim 1, characterized in that: In the preparation of the quaternary ammonium amino acid derived corrosion inhibitor, the working conditions of ultraviolet irradiation are: irradiation under a 365nm ultraviolet lamp for 15-20 minutes.

6. The corrosion resistance treatment process for the surface of a remote plasma source cavity according to claim 1, characterized in that: In the preparation of the quaternary amino acid derived corrosion inhibitor, the mass ratio of the quaternary ammonium copolymer terminated with alkynyl and L-cysteine ​​is 4:2.1.

Citation Information

Patent Citations

  • Methods and Apparatus for Protecting Plasma Chamber Surfaces

    US20110005922A1

  • KR20230007157A